2022
DOI: 10.1155/2022/5122448
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Ononin by Modulation of Apoptosis in Non-Small-Cell Lung Cancer through Inhibiting PI3K/Akt/mTOR Pathway

Abstract: Lung cancer is a leading global cause of cancer-related death in both males and females. Non-small-cell lung cancer (NSCLC) is the most commonly diagnosed cancer type that can be difficult to control with conventional chemotherapeutic and surgical approaches resulting in a poor prognosis. Paclitaxel (PTX) is a commonly used chemotherapeutic drug for NSCLC, which can cause tissue injury in healthy cells and affect the quality of life in patients with cancer. In order to treat NSCLC, alternative medications with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In recent years, more and more research studies have been conducted on the relationship between ROS and cancer. ROS is considered to be an important anticancer target due to the different roles of different levels of ROS in various stages of cancer development, and many studies have shown that therapeutic strategies targeting ROS are significantly effective in the treatment of various diseases, including human lung cancer, colorectal cancer, breast cancer, and glioblastoma [ 61 , 132 , 133 , 134 ]. Therefore, based on the effectiveness of excessive ROS for cancer treatment, new anticancer therapies targeting ROS generation can be regarded as a good solution to the current problems of cancer drug resistance and the low efficacy of traditional anticancer therapies.…”
Section: Cancer Therapeutic Strategies Targeting Ros Generationmentioning
confidence: 99%
“…In recent years, more and more research studies have been conducted on the relationship between ROS and cancer. ROS is considered to be an important anticancer target due to the different roles of different levels of ROS in various stages of cancer development, and many studies have shown that therapeutic strategies targeting ROS are significantly effective in the treatment of various diseases, including human lung cancer, colorectal cancer, breast cancer, and glioblastoma [ 61 , 132 , 133 , 134 ]. Therefore, based on the effectiveness of excessive ROS for cancer treatment, new anticancer therapies targeting ROS generation can be regarded as a good solution to the current problems of cancer drug resistance and the low efficacy of traditional anticancer therapies.…”
Section: Cancer Therapeutic Strategies Targeting Ros Generationmentioning
confidence: 99%
“…The results showed that a dose‐dependent manner treatment with ononin synergistically with or without PTX significantly inhibited the proliferation of A549 and HCC827 cells. [ 3 ] Furthermore, cotreatment of ononin with PTX significantly increased the rate of cell death and ROS generation and decreased MMPs in human lung cancer A549 and HCC827 cells. [ 3 ] The production of ROS can also promote anti‐tumorigenic effects, initiating oxidative stress‐induced tumor cell death.…”
Section: Synergistic Interactions Of Ononin In Cancermentioning
confidence: 99%
“…[2] It has demonstrated anti-inflammatory, antiproliferative, proapoptotic, antiangiogenic, and antimetastatic effects across diverse cancer models, including lung, laryngeal, colon, breast, and osteosarcoma. [1,[3][4][5][6] Ononin targets multiple molecular pathways, hindering malignant development and tumor growth. [3] This review compiles and systematically presents current knowledge about ononin's anticancer potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a wide range of biological effects, such as antioxidant, antidiabetic, anti-obesity, neuroprotective, cardioprotective, antiviral, and anti-inflammatory qualities [11][12][13][14][15][16]. Ononin exhibits dose-and time-dependent manners of anti-cancer effects, including the larynx [17], colon [18], lung [19], and breast [20]. In addition, ononin inhibited ER stress and apoptosis, likely activating the SIRT3 pathway, and protected against doxorubicin-induced cardiotoxicity [21].…”
Section: Introductionmentioning
confidence: 99%